Preparation method of CuSatC / MoS2 composite material
Through the preparation of CuS@C/MoS2 composite materials, the problem of high cost of existing electrocatalytic hydrogen evolution reaction catalysts is solved, and low-cost and efficient electrocatalytic hydrogen evolution performance is achieved, with good application prospects and non-toxic and harmless properties.
Patent Information
- Application Number
- CN202411251627.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-08
- Publication Date
- 2025-01-14
- Estimated Expiration
- 2044-09-08
AI Technical Summary
The existing electrocatalytic hydrogen evolution reaction catalysts are costly and not abundant, making it difficult to achieve low-cost and efficient catalyst design.
CuS@C/MoS2 composite material is used to prepare copper oxide through raw materials such as copper sulfate, sodium citrate, sodium hydroxide and dopamine at room temperature, and then calcined in an argon atmosphere to form a carbon shell covering and passes through hydrothermal heat. The reaction produces molybdenum sulfide to form a CuS@C/MoS2 composite material.
It realizes a catalyst with low cost, simple preparation process, excellent electrocatalytic hydrogen evolution performance, with good application prospects and non-toxic and harmless properties.
Smart Images

Figure CN119307951A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of electrocatalytic materials, and in particular to a method for preparing a CuS@C / MoS2 composite material. Background Art
[0002] The increasingly severe global energy crisis and environmental pollution require the pursuit of economic, sustainable and efficient energy. Hydrogen has a high calorific value (1.4×10 8 J / kg) and environmentally friendly properties, it is considered to be one of the most promising renewable green energy sources. In hydrogen production technology, the electrocatalytic hydrogen evolution reaction has attracted much attention due to its ability to produce high-purity hydrogen and drive green energy. Catalysts are the core of the electrocatalytic hydrogen production process and can reduce the potential barrier of the electrocatalytic water decomposition reaction. It is generally believed that an efficient catalyst should have a H* absorption Gibbs free energy close to thermoneutrality (i.e., ΔG H* ≈0). Most catalysts designed for electrocatalytic water splitting to produce hydrogen are based on precious metals, such as platinum compounds, but their high cost and almost non-abundance limit their widespread use. Therefore, it is imperative to develop a low-cost and efficient catalyst in the field of electrocatalytic hydrogen evolution reaction.
[0003] The present invention provides a CuS@C / MoS2 composite material. A Cu2O@PDA precursor is prepared at room temperature by a simple method, and then PDA is transformed into a carbon shell uniformly coated on the surface of cuprous oxide (Cu2O@C) by heat treatment in a tubular furnace, and finally molybdenum sulfide is grown on the surface of Cu2O@C by a hydrothermal reaction to obtain a CuS@C / MoS2 composite material. The prepared composite catalyst has good electrical conductivity and catalytic activity, and has low production cost, simple preparation process, short production cycle, and good application potential in the field of electrocatalytic hydrogen production. Summary of the invention
[0004] The purpose of the present invention is to provide a method for preparing an electrocatalyst with low cost and excellent electrocatalytic hydrogen evolution performance.
[0005] To achieve the above object, the present invention provides a method for preparing a CuS@C / MoS2 composite material, comprising the following steps:
[0006] Step S1, dissolving copper sulfate and sodium citrate in a certain amount of deionized water to obtain solution A; adding a certain concentration of sodium hydroxide solution dropwise to solution A while stirring to obtain solution B;
[0007] Step S2, after stirring solution B for a certain period of time, adding a certain concentration of ascorbic acid solution dropwise while stirring solution B to obtain solution C, stirring and aging at room temperature for a certain period of time, collecting the product by centrifugation, washing with water and ethanol for several times, and drying to obtain cuprous oxide;
[0008] Step S3, dispersing cuprous oxide in a certain amount of methanol to obtain a cuprous oxide-methanol solution, adding a certain concentration of dopamine (DA)-methanol solution to the cuprous oxide-methanol solution under stirring to obtain a D solution; stirring the D solution at an appropriate temperature for a certain period of time, collecting the product by centrifugation, washing it with ethanol for several times, and drying it to obtain polydopamine-coated cuprous oxide (Cu2O@PDA);
[0009] Step S4, placing the Cu2O@PDA powder in a tube furnace and heating it in flowing argon (Ar) to obtain Cu2O@C powder;
[0010] Step S5, dissolving Cu2O@C powder in a certain amount of deionized water to prepare a Cu2O@C aqueous solution, adding a certain amount of ammonium molybdate and thiourea to the Cu2O@C aqueous solution to obtain an E solution, and stirring for a certain time; transferring the E solution to a reactor, performing a hydrothermal reaction at a certain temperature for a period of time, and then cooling to room temperature, collecting the product by centrifugation, washing with ethanol and water for several times, and drying to obtain a CuS@C / MoS2 composite material.
[0011] Preferably, in step S1, the copper sulfate is copper sulfate pentahydrate, the molar ratio of the copper sulfate to the sodium citrate is 3:1-10:3, the deionized volume is 50-100 mL, the concentration of the sodium hydroxide solution is 0.15-2.4 mol / L, the dropping speed is 5-15 mL / min, and the stirring time is 5-30 min.
[0012] Preferably, in step S2, the concentration of the ascorbic acid solution is 0.01-0.1 mol / L, the dropping speed is 5-15 mL / min, and the aging time is 30-90 min.
[0013] Preferably, in step S3, the concentration of the dopamine (DA)-methanol solution is 0.01-0.05 mol / L, the dropping speed is 5-15 mL / min, the mass of the cuprous oxide is 200-400 mg, the volume of the methanol is 350-450 mL, the heating temperature is 55-65° C., and the heating time is 6-9 h.
[0014] Preferably, in step S4, the heating temperature is 600-900°C, the heating time is 1-3h, and the heating rate is 4-7°C / min.
[0015] Preferably, in step S5, the ammonium molybdate is ammonium heptamolybdate tetrahydrate, the mass ratio of the Cu2O@C, the ammonium heptamolybdate tetrahydrate and the thiourea is (1.1-1.3):(20-30):(8-106), the hydrothermal temperature is 160-220°C, and the reaction time is 12-32h.
[0016] Preferably, in step S5, the CuS@C / MoS2 composite material is spherical in shape, and its surface includes 1T phase molybdenum sulfide and 2H phase molybdenum sulfide.
[0017] The present invention uses copper sulfate, sodium citrate, methanol, sodium hydroxide solution, DA solution and ascorbic acid solution as raw materials, and prepares the precursor Cu2O@PDA by a solution method. Due to the presence of sodium citrate, copper ions and citrate radicals form a complex during the reaction, which helps to control the generation rate of cuprous oxide, thereby obtaining cubic cuprous oxide with uniform size. The catechol group of dopamine is combined with the Cu in Cu2O by a coordination-polymerization mechanism. 1+ The coordination effect makes dopamine have strong adhesion, resulting in the formation of dopamine on the Cu2O surface; because the methanol solvent is alkaline, the increase in temperature triggers the polymerization of dopamine to obtain polydopamine (PDA). The synthesized polydopamine (PDA) contains catechol groups, which can further bind to the Cu of Cu2O. 1+ Coordination, thereby continuing to promote the polymerization of polydopamine on Cu2O, namely the Cu2O@PDA sample. Carbon shell-coated cuprous oxide (Cu2O@C) was obtained by calcining Cu2O@PDA under an argon atmosphere to protect cuprous oxide, improve the durability and stability of cuprous oxide, and form a conductive channel between cuprous oxide, promote the flow of electrons, and increase the current density. Using Cu2O@C as a precursor, a long sheet of molybdenum sulfide on the ball was formed by a one-step hydrothermal method with ammonium molybdate and thiourea, which was rich in 1T phase molybdenum sulfide and 2H phase molybdenum sulfide. The built-in electric field at the interface of the heterostructure of 1T phase molybdenum sulfide and 2H phase molybdenum sulfide can improve the conductivity and carrier transport capacity of the composite catalyst. By controlling the interlayer distance and reaction temperature during the synthesis of molybdenum sulfide, the directional transformation of 2H phase molybdenum sulfide to 1T phase molybdenum sulfide can be better achieved, thereby significantly increasing the active sites and conductivity, accelerating the adsorption-dissociation of hydrogen, and obtaining better electrocatalytic hydrogen production performance. The CuS@C / MoS2 composite material provided by the present invention has low cost, simple preparation process, short preparation cycle, excellent electrocatalytic hydrogen evolution performance, is non-toxic and harmless, and has good application prospects.
[0018] The present invention also provides a CuS@C / MoS2 composite material, which is prepared by the preparation method of the CuS@C / MoS2 composite material as described above. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 Schematic diagram of the process of preparing the CuS@C / MoS2 composite material in an embodiment of the present invention;
[0020] Figure 2X-ray diffraction patterns of the CuS@C / MoS2 composite material in Example 1 of the present invention, the molybdenum sulfide in Comparative Example 1, the copper sulfide / molybdenum sulfide composite catalyst in Comparative Example 2, and the CuS@PDA / MoS2 composite material in Comparative Example 3;
[0021] Figure 3 This is a Raman spectrum of the CuS@C / MoS2 composite material in Example 1 of the present invention;
[0022] FIG4 is a scanning electron microscope image of the CuS@C / MoS2 composite material in Example 1 of the present invention and the molybdenum sulfide catalyst in Comparative Example 1;
[0023] Figure 5 It is a comparison diagram of polarization curves of samples prepared in Example 1, Example 2, Comparative Example 1, Comparative Example 2 and Comparative Example 3 in 0.5M H2SO4 electrolyte;
[0024] Figure 6 It is a comparison diagram of the Tafel curves of the samples prepared in Example 1, Example 2, Comparative Example 1, Comparative Example 2 and Comparative Example 3 in 0.5M H2SO4 electrolyte. DETAILED DESCRIPTION
[0025] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, specific embodiments of the present invention are described in detail below.
[0026] It should be noted that, in the absence of conflict, the features in the embodiments of the present invention can be combined with each other. The meanings of the terms "comprising", "including", "containing", and "having" are non-restrictive, that is, other steps and other ingredients that do not affect the results can be added. The above terms cover the terms "consisting of" and "essentially consisting of". Unless otherwise specified, materials, equipment, and reagents are commercially available.
[0027] The present invention provides a method for preparing a CuS@C / MoS2 composite material. Figure 1 As shown, the following steps are included:
[0028] Step S1, dissolving copper sulfate and sodium citrate in a certain amount of deionized water to prepare a first mixed solution;
[0029] Step S1, dissolving copper sulfate and sodium citrate in a certain amount of deionized water to obtain solution A; adding a certain concentration of sodium hydroxide solution dropwise while stirring solution A to obtain solution B;
[0030] Step S2, after stirring solution B for a certain period of time, adding a certain concentration of ascorbic acid solution dropwise while stirring solution B to obtain solution C, stirring and aging at room temperature for a certain period of time, collecting the product by centrifugation, washing with water and ethanol for several times, and drying to obtain cuprous oxide;
[0031] Step S3, dispersing cuprous oxide in a certain amount of methanol to obtain a cuprous oxide-methanol solution, adding a certain concentration of dopamine (DA)-methanol solution to the cuprous oxide-methanol solution under stirring to obtain a D solution; stirring the D solution at an appropriate temperature for a certain period of time, collecting the product by centrifugation, washing it with ethanol for several times, and drying it to obtain polydopamine-coated cuprous oxide (Cu2O@PDA);
[0032] Step S4, placing the Cu2O@PDA powder in a tube furnace and heating it in flowing argon (Ar) to obtain Cu2O@C powder;
[0033] Step S5, dissolving Cu2O@C powder in a certain amount of deionized water to prepare a Cu2O@C aqueous solution, adding a certain amount of ammonium molybdate and thiourea to the Cu2O@C aqueous solution to obtain an E solution, and stirring for a certain time; transferring the E solution to a reactor, performing a hydrothermal reaction at a certain temperature for a period of time, and then cooling to room temperature, collecting the product by centrifugation, washing with ethanol and water for several times, and drying to obtain a CuS@C / MoS2 composite material.
[0034] The present invention uses copper sulfate, sodium citrate, methanol, sodium hydroxide solution, DA solution and ascorbic acid solution as raw materials, and prepares the precursor Cu2O@PDA by a solution method. Due to the presence of sodium citrate, copper ions and citrate radicals form a complex during the reaction, which helps to control the generation rate of cuprous oxide, thereby obtaining cubic cuprous oxide with uniform size. The catechol group of dopamine is combined with the Cu in Cu2O by a coordination-polymerization mechanism. 1+ The coordination effect makes dopamine have strong adhesion, resulting in the formation of dopamine on the Cu2O surface; because the methanol solvent is alkaline, the increase in temperature triggers the polymerization of dopamine to obtain polydopamine (PDA). The synthesized polydopamine (PDA) contains catechol groups, which can further bind to the Cu of Cu2O. 1+Coordination, thereby continuing to promote the polymerization of polydopamine on Cu2O, namely the Cu2O@PDA sample. Carbon shell-coated cuprous oxide (Cu2O@C) was obtained by calcining Cu2O@PDA under an argon atmosphere to protect cuprous oxide, improve the durability and stability of cuprous oxide, and form a conductive channel between cuprous oxide, promote the flow of electrons, and increase the current density. Using Cu2O@C as a precursor, a long sheet of molybdenum sulfide on the ball was formed by a one-step hydrothermal method with ammonium molybdate and thiourea, which was rich in 1T phase molybdenum sulfide and 2H phase molybdenum sulfide. The built-in electric field at the interface of the heterostructure of 1T phase molybdenum sulfide and 2H phase molybdenum sulfide can improve the conductivity and carrier transport capacity of the composite catalyst. By controlling the interlayer distance and reaction temperature during the synthesis of molybdenum sulfide, the directional transformation of 2H phase molybdenum sulfide to 1T phase molybdenum sulfide can be better achieved, thereby significantly increasing the active sites and conductivity, accelerating the adsorption-dissociation of hydrogen, and obtaining better HER performance. The CuS@C / MoS2 composite material provided by the present invention has low cost, simple preparation process, short preparation cycle, excellent electrocatalytic hydrogen evolution performance, is non-toxic and harmless, and has good application prospects.
[0035] In step S1, the copper sulfate is copper sulfate pentahydrate, the molar ratio of the copper sulfate to the sodium citrate is 3:1-10:3, the deionized volume is 50-100 mL, the concentration of the sodium hydroxide solution is 0.15-2.4 mol / L, the dropping speed is 5-15 mL / min, and the stirring time is 5-30 min.
[0036] Illustratively, the copper sulfate is anhydrous copper sulfate, (10-13):1 mmol sodium citrate is dissolved in 50-100 mL deionized water, stirred for 5-30 min to fully mix, to obtain solution A, and while solution A is stirred, a sodium hydroxide solution with a concentration of 0.15-2.4 mol / L is added dropwise to obtain solution B.
[0037] In step S2, the concentration of the ascorbic acid solution is 0.01-0.1 mol / L, the dropping speed is 5 mL / min, the stirring time is 3-5 min, and the aging time is 30-90 min.
[0038] Exemplarily, after stirring solution B for 5-30 minutes, an ascorbic acid solution with a concentration of 0.01-0.1 mol / L is added dropwise to solution B to obtain solution C at a dropping rate of 5 mL / min. After stirring for 3-5 minutes, the solution is aged at room temperature for 30-90 minutes. The precipitate is then separated, washed several times with ethanol and deionized water to remove impurities, and dried in an oven at 60° C. for 12 hours. After grinding, cuprous oxide is obtained.
[0039] In step S3, the mass of the cuprous oxide is 200-400 mg, the volume of the methanol is 350-450 mL, the concentration of the dopamine (DA)-methanol solution is 0.01-0.05 mol / L, the dropping speed is 5-15 mL / min, the heating temperature is 55-65° C., and the heating time is 6-9 h.
[0040] Exemplarily, 200-400 mg of cuprous oxide is dispersed in 350-450 mL of methanol, and then a dopamine (DA)-methanol solution with a concentration of 0.01-0.05 mol / L is added dropwise to obtain a D solution. The D solution is stirred at 60 ° C for 7 h. The product is collected by centrifugation for 3 min (10000 rpm), washed several times with methanol, and dried at 65 ° C for 8 h. To obtain polydopamine-coated cuprous oxide (Cu2O@PDA).
[0041] In step S4, the heating temperature is 600-900°C, the heating time is 1-3h, and the heating rate is 4-7°C / min.
[0042] Exemplarily, Cu2O@PDA powder is placed in a tube furnace and heated to 600-900°C at a heating rate of 4-7°C / min in flowing Ar for 1-3h to prepare Cu2O@C to obtain a Cu2O@C precursor.
[0043] In step S5, the ammonium molybdate is tetrahydrated ammonium heptamolybdate, the mass ratio of the Cu2O@C, the tetrahydrated ammonium heptamolybdate and the thiourea is (1.1-1.3):(20-30):(8-106), the hydrothermal temperature is 160-220°C, and the reaction time is 12-32h.
[0044] For example, the ammonium molybdate is tetrahydrated ammonium heptamolybdate, 1.1-1.3 parts of Cu2O@C catalyst are mixed with 28-32 mL of deionized water to obtain a mixed reaction, and then 20-30 parts of tetrahydrated ammonium heptamolybdate and 8-50 parts of thiourea are stirred for 5-30 minutes to obtain solution E. The solution E is transferred to a reactor and reacted at a temperature of 160-220° C. for 12-32 hours.
[0045] By controlling the reaction temperature within the range of 160-220°C and controlling the interlayer distance during the synthesis of molybdenum sulfide, the directional transformation of 2H phase molybdenum sulfide to 1T phase molybdenum sulfide can be better achieved, thereby significantly increasing the active sites and conductivity, accelerating the adsorption-dissociation of hydrogen, and obtaining better electrocatalytic hydrogen production performance.
[0046] The present invention will be further described below in conjunction with specific examples. It should be understood that these examples are only used to illustrate the present invention and are not intended to limit the scope of the present invention. The experimental methods in the following examples without specifying specific conditions are usually based on the conditions recommended by the manufacturer.
[0047] Example 1
[0048] 1.1. Dissolve 1.5 mmol of anhydrous copper sulfate and 0.5 mmol of sodium citrate in 80 mL of deionized water and stir for 15 min to obtain solution A. Add 20 mL of 1.25 M NaOH solution dropwise to solution A under stirring and stir for 15 min to obtain solution B.
[0049] 1.2. Add 50 mL of 0.03 M ascorbic acid solution to solution B, stir for 3 min, and obtain solution C. Then age the solution at room temperature for 1 h to form a brick-red precipitate. Collect the brick-red precipitate, wash it with water and ethanol several times, dry it, and grind it to obtain cubic cuprous oxide.
[0050] 1.3. Disperse 300 mg of cuprous oxide in 375 mL of methanol, then add 75 mL of 20 mM DA methanol solution to obtain solution D, and stir solution D at 60 ° C for 7 h. Collect the product by centrifugation for 3 min (10000 rpm), wash with ethanol several times, and dry at 65 ° C for 8 h to obtain polydopamine-coated cuprous oxide (Cu2O@PDA).
[0051] 1.4. Place the Cu2O@PDA powder in a tube furnace and heat it to 750°C for 2h at a heating rate of 5°C / min in flowing Ar to prepare Cu2O@C. To obtain a Cu2O@C catalyst prepared using Cu2O@C as a precursor.
[0052] 1.5. Mix 60 mg of Cu2O@C and 28 mL of deionized water to obtain a mixed aqueous solution, then add 1.02 g of ammonium heptamolybdate tetrahydrate and 0.4 g of thiourea to the mixed aqueous solution and stir to obtain solution E. Transfer solution E to a stainless steel reactor lined with Teflon, react at 220°C for 27 h, cool to room temperature, wash with ethanol and water for 3 times each, and vacuum dry at 60°C for 12 h to obtain a CuS@C / MoS2 composite catalyst.
[0053] Example 2
[0054] 2.1. Dissolve 1.5 mmol of anhydrous copper sulfate and 0.5 mmol of sodium citrate in 80 mL of deionized water and stir for 15 min to obtain solution A. Add 20 mL of 1.25 M NaOH solution dropwise to solution A under stirring and stir for 15 min to obtain solution B.
[0055] 2.2. Add 50 mL of 0.03 M ascorbic acid solution to solution B, stir for 3 min, and obtain solution C. Then, age the solution at room temperature for 1 h to form a brick-red precipitate. Collect the brick-red precipitate, wash it with water and ethanol several times, dry it, and grind it to obtain cubic cuprous oxide.
[0056] 2.3. Disperse 300 mg of cuprous oxide in 375 mL of methanol, then add 75 mL of 20 mM DA methanol solution to obtain solution D, and stir solution D at 60 ° C for 7 h. Collect the product by centrifugation for 3 min (10000 rpm), wash with ethanol several times, and dry at 65 ° C for 8 h to obtain polydopamine-coated cuprous oxide (Cu2O@PDA).
[0057] 2.4. The Cu2O@PDA powder was placed in a tube furnace and heated to 750°C for 2h at a heating rate of 5°C / min in flowing Ar to prepare Cu2O@C. The Cu2O@C catalyst was prepared using Cu2O@C as a precursor.
[0058] 2.5. Mix 50 mg of Cu2O@C and 28 mL of deionized water to obtain a mixed aqueous solution, then add 1.02 g of ammonium heptamolybdate tetrahydrate and 0.4 g of thiourea to the mixed aqueous solution and stir to obtain solution E. Transfer solution E to a stainless steel reactor lined with Teflon, react at 220°C for 27 h, cool to room temperature, wash with ethanol and water for 3 times each, and vacuum dry at 60°C for 12 h to obtain a CuS@C / MoS2 composite catalyst.
[0059] Example 3
[0060] 3.1. Dissolve 1.5 mmol of anhydrous copper sulfate and 0.5 mmol of sodium citrate in 80 mL of deionized water and stir for 15 min to obtain solution A. Add 20 mL of 1.25 M NaOH solution dropwise to solution A under stirring and stir for 15 min to obtain solution B.
[0061] 3.2. Add 50 mL of 0.03 M ascorbic acid solution to solution B, stir for 3 min, and obtain solution C. Then, age the solution at room temperature for 1 h to form a brick-red precipitate. Collect the brick-red precipitate, wash it with water and ethanol several times, dry it, and grind it to obtain cubic cuprous oxide.
[0062] 3.3. Disperse 300 mg of cuprous oxide in 375 mL of methanol, then add 75 mL of 40 mM DA methanol solution to obtain solution D, and stir solution D at 60 ° C for 7 h. Collect the product by centrifugation for 3 min (10000 rpm), wash with ethanol several times, and dry at 65 ° C for 8 h to obtain polydopamine-coated cuprous oxide (Cu2O@PDA).
[0063] 3.4. The Cu2O@PDA powder was placed in a tube furnace and heated to 750°C for 2h at a heating rate of 5°C / min in flowing Ar to prepare Cu2O@C. The Cu2O@C catalyst was prepared using Cu2O@C as a precursor.
[0064] 3.5. Mix 60 mg of Cu2O@C and 28 mL of deionized water to obtain a mixed aqueous solution, then add 1.02 g of ammonium heptamolybdate tetrahydrate and 0.4 g of thiourea to the mixed aqueous solution and stir to obtain solution E. Transfer solution E to a stainless steel reactor lined with Teflon, react at 220°C for 27 h, cool to room temperature, wash with ethanol and water for 3 times each, and vacuum dry at 60°C for 12 h to obtain a CuS@C / MoS2 composite catalyst.
[0065] Example 4
[0066] 4.1. Dissolve 1.65 mmol of anhydrous copper sulfate and 0.4 mmol of sodium citrate in 100 mL of deionized water and stir for 15 min to obtain solution A. Add 20 mL of 1.05 M NaOH solution dropwise to solution A under stirring and stir for 15 min to obtain solution B.
[0067] 4.2. Add 40 mL of 0.05 M ascorbic acid solution to solution B and stir for 3 min to obtain solution C. Then age the solution at room temperature for 1 h to form a brick-red precipitate. Collect the brick-red precipitate, wash it with water and ethanol several times, dry it, and grind it to obtain cubic cuprous oxide.
[0068] 4.3. Disperse 300 mg of cuprous oxide in 400 mL of methanol, then add 75 mL of 20 mM DA methanol solution to obtain solution D, and stir solution D at 65 ° C for 7 h. Collect the product by centrifugation for 3 min (10000 rpm), wash with ethanol several times, and dry at 65 ° C for 8 h to obtain polydopamine-coated cuprous oxide (Cu2O@PDA).
[0069] 4.4. The Cu2O@PDA powder was placed in a tube furnace and heated to 850°C for 2h at a heating rate of 4°C / min in flowing Ar to prepare Cu2O@C. The Cu2O@C catalyst was prepared using Cu2O@C as a precursor.
[0070] 4.5. Mix 70 mg of Cu2O@C and 28 mL of deionized water to obtain a mixed aqueous solution, then add 1.02 g of ammonium heptamolybdate tetrahydrate and 0.4 g of thiourea to the mixed aqueous solution and stir to obtain solution E. Transfer solution E to a stainless steel reactor lined with Teflon, react at 220°C for 27 h, cool to room temperature, wash with ethanol and water for 3 times each, and vacuum dry at 60°C for 12 h to obtain a CuS@C / MoS2 composite catalyst.
[0071] Example 5
[0072] 5.1. Dissolve 1.65 mmol of anhydrous copper sulfate and 0.5 mmol of sodium citrate in 80 mL of deionized water and stir for 15 min to obtain solution A. Add 30 mL of 1.25 M NaOH solution dropwise to solution A under stirring and stir for 15 min to obtain solution B.
[0073] 5.2. Add 80 mL of 0.03 M ascorbic acid solution to solution B and stir for 3 min to obtain solution C. Then age the solution at room temperature for 1 h to form a brick-red precipitate. Collect the brick-red precipitate, wash it with water and ethanol several times, dry it, and grind it to obtain cubic cuprous oxide.
[0074] 5.3. Disperse 275 mg of cuprous oxide in 350 mL of methanol, then add 100 mL of 20 mM DA methanol solution to obtain solution D, and stir solution D at 65 ° C for 7 h. Collect the product by centrifugation for 3 min (10000 rpm), wash with ethanol several times, and dry at 65 ° C for 8 h to obtain polydopamine-coated cuprous oxide (Cu2O@PDA).
[0075] 5.4. Place the Cu2O@PDA powder in a tube furnace and heat it to 750°C for 2h at a heating rate of 4°C / min in flowing Ar to prepare Cu2O@C. To obtain a Cu2O@C catalyst prepared using Cu2O@C as a precursor.
[0076] 5.5. Mix 60 mg of Cu2O@C and 28 mL of deionized water to obtain a mixed aqueous solution, then add 1.02 g of ammonium heptamolybdate tetrahydrate and 0.4 g of thiourea to the mixed aqueous solution and stir to obtain solution E. Transfer solution E to a stainless steel reactor lined with Teflon, react at 220°C for 24 h, cool to room temperature, wash with ethanol and water for 3 times each, and vacuum dry at 60°C for 12 h to obtain a CuS@C / MoS2 composite catalyst.
[0077] Comparative Example 1
[0078] 1.1. Dissolve 1.02 g of ammonium heptamolybdate tetrahydrate in 28 mL of deionized water, add 0.4 g of thiourea and stir until the solution is clear, transfer the solution to a stainless steel reactor lined with Teflon, react at 220°C for 27 h, cool to room temperature, wash with ethanol and water 3 times each, and dry in a vacuum drying oven at 60°C for 12 h to obtain flower-shaped molybdenum sulfide.
[0079] Comparative Example 2
[0080] 2.1. Dissolve 1.5 mmol of anhydrous copper sulfate and 0.5 mmol of sodium citrate in 80 mL of deionized water and stir for 15 min to obtain solution A. Add 20 mL of 1.25 M NaOH solution dropwise to solution A under stirring and stir for 15 min to obtain solution B.
[0081] 2.2. Add 50 mL of 0.03 M ascorbic acid solution to solution B, stir for 3 min, and obtain solution C. Then, age the solution at room temperature for 1 h to form a brick-red precipitate. Collect the brick-red precipitate, wash it with water and ethanol several times, dry it, and grind it to obtain cubic cuprous oxide.
[0082] 2.3. Mix 60 mg of Cu2O and 28 mL of deionized water to obtain a mixed aqueous solution, then add 1.02 g of ammonium heptamolybdate tetrahydrate and 0.4 g of thiourea to the mixed aqueous solution and stir to obtain a solution D;
[0083] 2.5. Transfer solution D to a stainless steel reactor lined with Teflon, react at 220°C for 27 hours, cool to room temperature, wash with ethanol and water three times each, and vacuum dry at 60°C for 12 hours to obtain a molybdenum sulfide / copper sulfide composite catalyst.
[0084] Comparative Example 3
[0085] 3.1. Dissolve 1.5 mmol of anhydrous copper sulfate and 0.5 mmol of sodium citrate in 80 mL of deionized water and stir for 15 min to obtain solution A. Add 20 mL of 1.25 M NaOH solution to solution A under stirring and stir for 15 min to obtain solution B.
[0086] 3.2. Add 50 mL of 0.03 M ascorbic acid solution to solution B, stir for 3 min, and obtain solution C. Then, age the solution at room temperature for 1 h to form a brick-red precipitate. Collect the brick-red precipitate, wash it with water and ethanol several times, dry it, and grind it to obtain cubic cuprous oxide.
[0087] 3.3. Disperse 300 mg of cuprous oxide in 375 mL of methanol, and then add 75 mL of 20 mM DA methanol solution to obtain solution D. Thereafter, solution D was stirred at 60 °C for 7 h. The product was collected by centrifugation for 3 min (10000 rpm), washed several times with ethanol, and dried at 65 °C for 8 h to obtain polydopamine-coated cuprous oxide (Cu2O@PDA).
[0088] 3.4. Mix 60 mg of Cu2O@PDA and 28 mL of deionized water to obtain a Cu2O@PDA aqueous solution, then add 1.02 g of ammonium heptamolybdate tetrahydrate and 0.4 g of thiourea to the Cu2O@PDA aqueous solution and stir to form a fifth mixed solution. Transfer the fifth mixed solution to a stainless steel reactor lined with Teflon, react at 220°C for 27 hours, cool to room temperature, wash with ethanol and water three times each, and vacuum dry at 60°C for 12 hours to obtain a CuS@PDA / MoS2 composite catalyst.
[0089] Experimental Example 1
[0090] The CuS@C / MoS2 composite catalyst obtained in Example 1 was subjected to X-ray diffraction analysis and observed by scanning electron microscopy.
[0091] Figure 2 The X-ray diffraction patterns of the CuS@C / MoS2 composite catalyst in Example 1, the molybdenum sulfide catalyst in Comparative Example 1, the copper sulfide / molybdenum sulfide composite catalyst in Comparative Example 2, and the CuS@PDA / MoS2 composite catalyst in Comparative Example 3 are shown in Table 1. Figure 2 It can be seen that the X-ray diffraction peaks appearing in Example 1, Comparative Example 1, Comparative Example 2 and Comparative Example 3 all correspond to the standard molybdenum sulfide diffraction peaks and the standard copper sulfide diffraction peaks, indicating that the composite catalysts prepared in Example 1, Comparative Example 2 and Comparative Example 3 contain both molybdenum sulfide and copper sulfide.
[0092] Figure 3The Raman spectrum of the CuS@C / MoS2 composite material in Example 1 of the present invention is shown in FIG. Figure 5 J1, J2, and E of 1T phase MoS can be observed. 1g and characteristic peaks of J3 vibration mode.
[0093] FIG4 is a scanning electron microscope image of the CuS@C / MoS2 composite catalyst in Example 1. Figure 3 It can be seen that its microscopic morphology is cubic flower ball-shaped.
[0094] FIG4 is a scanning electron microscope image of the CuS@C / MoS2 composite material in Example 1 of the present invention and the molybdenum sulfide in Comparative Example 1, Figure 3 (a) and Figure 3 (b) are scanning electron micrographs of the molybdenum sulfide in Comparative Example 1 and the CuS@C / MoS2 composite material obtained in Example 1. Figure 3 It can be analyzed that compared with the molybdenum sulfide in Comparative Example 1, the molybdenum sulfide in the CuS@C / MoS2 composite material in Example 1 grows more uniformly and densely, and more active sites on the edge of the molybdenum sulfide are exposed, thereby improving the catalytic activity.
[0095] Experimental Example 2
[0096] The samples prepared in Example 1, Example 2, Example 3, Comparative Example 1, Comparative Example 2 and Comparative Example 3 were respectively tested for their performance of hydrogen evolution reaction by electrolysis of water. The specific test method is as follows: the materials prepared in Example 1, Example 2, Example 3, Comparative Example 1, Comparative Example 2 and Comparative Example 3 were respectively made into working electrodes for electrocatalytic hydrogen evolution reaction, a saturated calomel electrode was used as a reference electrode, and a platinum electrode was used as a counter electrode to form a three-electrode system, which was connected to an electrochemical workstation in a H2SO4 electrolyte with a concentration of 0.5 mol / L to test the electrocatalytic hydrogen evolution performance of the material, and the HER polarization curve of the sample was studied at a scanning speed of 50 mV / s.
[0097] The test results are as follows Figure 5 and Figure 6 shown.
[0098] Figure 5 The polarization curves of the samples prepared in Example 1, Example 2, Example 3, Comparative Example 1, Comparative Example 2 and Comparative Example 3 in 0.5 mol / L H2SO4 electrolyte are compared. Figure 5 It can be seen that the CuS@C / MoS2 composite material prepared in Example 1 has a current density of 10 mA·cm -2 The overpotential of the molybdenum sulfide prepared in Comparative Example 1 is 39.5 mV at a current density of 10 mA cm -2The overpotential is 265.5 mV, indicating that the CuS@C / MoS2 composite material prepared in Example 1 has a smaller overpotential and can effectively reduce the reaction activation energy.
[0099] Figure 6 The Tafel curves of the samples prepared in Example 1, Example 2, Example 3, Comparative Example 1, Comparative Example 2 and Comparative Example 3 in 0.5 mol / L H2SO4 electrolyte are compared. Figure 6 It can be seen that Example 1 has a smaller Tafel slope, indicating that it can obtain a larger current when a smaller potential is applied. The CuS@C / MoS2 composite material prepared in Example 1 is more conducive to hydrogen evolution.
[0100] Although the present invention is disclosed as above, the protection scope of the present invention is not limited thereto. Those skilled in the art may make various changes and modifications without departing from the spirit and scope of the present invention, and these changes and modifications will fall within the protection scope of the present invention.
Claims
1. A method for preparing a CuS@C / MoS2 composite material, characterized in that: The following steps are involved: Step S1, dissolving copper sulfate and sodium citrate in a certain amount of deionized water to obtain solution A; adding a certain concentration of sodium hydroxide solution dropwise to solution A while stirring to obtain solution B; Step S2, after stirring solution B for a certain period of time, adding a certain concentration of ascorbic acid solution dropwise while stirring solution B to obtain solution C, stirring and aging at room temperature for a certain period of time, collecting the product by centrifugation, washing with water and ethanol for several times, and drying to obtain cuprous oxide; Step S3, dispersing cuprous oxide in a certain amount of methanol to obtain a cuprous oxide-methanol solution, adding a certain concentration of dopamine (DA)-methanol solution to the cuprous oxide-methanol solution under stirring to obtain a D solution; stirring the D solution at an appropriate temperature for a certain period of time, collecting the product by centrifugation, washing it with ethanol for several times, and drying it to obtain polydopamine-coated cuprous oxide (Cu2O@PDA); Step S4, placing the Cu2O@PDA powder in a tube furnace and heating it in flowing argon (Ar) to obtain Cu2O@C powder; Step S5, dissolving Cu2O@C powder in a certain amount of deionized water to prepare a Cu2O@C aqueous solution, adding a certain amount of ammonium molybdate and thiourea to the Cu2O@C aqueous solution to obtain an E solution, and stirring for a certain time; transferring the E solution to a reactor, performing a hydrothermal reaction at a certain temperature for a period of time, and then cooling to room temperature, collecting the product by centrifugation, washing with ethanol and water for several times, and drying to obtain a CuS@C / MoS2 composite material.
2. The method for preparing the CuS@C / MoS2 composite material according to claim 1, characterized in that: In the step S1, the copper sulfate is copper sulfate pentahydrate, the molar ratio of the copper sulfate to the sodium citrate is 3:1-10:3, the deionized volume is 50-100 mL, the concentration of the sodium hydroxide solution is 0.15-2.4 mol / L, the dropping speed is 5-15 mL / min, and the stirring time is 5-30 min.
3. The method for preparing the CuS@C / MoS2 composite material according to claim 1, characterized in that: In step S2, the concentration of the ascorbic acid solution is 0.01-0.1 mol / L, the dropping speed is 5-15 mL / min, the stirring time is 3-5 min, and the aging time is 30-90 min.
4. The method for preparing the CuS@C / MoS2 composite material according to claim 1, characterized in that: In the step S3, the mass of the cuprous oxide is 200-400 mg, the volume of the methanol is 350-450 mL, the concentration of the dopamine (DA)-methanol solution is 0.01-0.05 mol / L, the dropping speed is 5-15 mL / min, the heating temperature is 55-65° C., and the heating time is 6-9 h.
5. The method for preparing the CuS@C / MoS2 composite material according to claim 1, characterized in that: In step S4, the heating temperature is 600-900°C, the heating time is 1-3h, and the heating rate is 4-7°C / min.
6. The method for preparing the CuS@C / MoS2 composite material according to claim 1, characterized in that: In the step S5, the ammonium molybdate is ammonium heptamolybdate tetrahydrate, the mass ratio of the Cu2O@C, the ammonium heptamolybdate tetrahydrate and the thiourea is (1.1-1.3):(20-30):(8-106), the hydrothermal temperature is 160-220°C, and the reaction time is 12-32h.
7. A CuS@C / MoS2 composite material, characterized in that: The CuS@C / MoS2 composite material is prepared by the preparation method according to any one of claims 1 to 6.
8. The CuS@C / MoS2 composite material according to claim 7, characterized in that The CuS@C / MoS2 composite material is spherical in shape, and its surface includes 1T phase molybdenum sulfide and 2H phase molybdenum sulfide.
Citation Information
Patent Citations
Molybdenum sulfide / copper sulfide composite catalyst, working electrode and preparation method thereof
CN116497394A
Preparation method of polydopamine modified dimethylimidazole cobalt / molybdenum sulfide composite material
CN117583032A